2000
DOI: 10.1074/jbc.m910172199
|View full text |Cite
|
Sign up to set email alerts
|

Processing by Endoplasmic Reticulum Mannosidases Partitions a Secretion-impaired Glycoprotein into Distinct Disposal Pathways

Abstract: In the early secretory pathway, a distinct set of processing enzymes and family of lectins facilitate the folding and quality control of newly synthesized glycoproteins. In this regard, we recently identified a mechanism in which processing by endoplasmic reticulum mannosidase I, which attenuates the removal of glucose from asparagine-linked oligosaccharides, sorts terminally misfolded ␣ 1 -antitrypsin for proteasome-mediated degradation in response to its abrogated physical dissociation from calnexin (Liu, Y.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 57 publications
1
115
0
Order By: Relevance
“…The mechanism of degradation of ER-retained Z ␣ 1 -antitrypsin is controversial, with evidence both in favor and against proteasomal degradation (41,(43)(44)(45). In addition, a nonproteasomal degradation pathway and autophagy have been proposed as disposal pathways for Z ␣ 1 -antitrypsin (29,41,45).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of degradation of ER-retained Z ␣ 1 -antitrypsin is controversial, with evidence both in favor and against proteasomal degradation (41,(43)(44)(45). In addition, a nonproteasomal degradation pathway and autophagy have been proposed as disposal pathways for Z ␣ 1 -antitrypsin (29,41,45).…”
Section: Discussionmentioning
confidence: 99%
“…Although retrograde translocation through the microsomal import channel has been proposed for some ER proteins, there is growing evidence for a mechanism in which the proteasome, as part of a multiprotein complex that forms a platform on the cytosolic side of the ER membrane, directly mediates extraction of substrates from the ER membrane. 19,20 Nevertheless, these early studies in yeast, mammalian cell lines and cell-free systems all indicated that the proteasomal pathway could not fully account for disposal of ATZ [16][17][18][21][22][23] -that is in the absence of proteasomal activity there was clear-cut residual and time-dependent degradation of ATZ.…”
Section: The Proteasomal and Autophagic Pathways Contribute To Disposmentioning
confidence: 99%
“…22 Moreover, there is evidence for non-proteosomal mechanisms for degradation of ␣1ATZ. 19 Cabral et al 23 have provided evidence for a nonproteosomal degradation pathway that is sensitive to tyrosine phosphatase inhibitors. We have shown that macroautophagy contributes to disposal of retained ␣1ATZ, using chemical inhibitors 24 and cell lines genetically engineered for deficient autophagy (unpublished observations).…”
Section: Degradation Of Mutant ␣1atz In the Ermentioning
confidence: 99%